Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2023)
A dataset listing the 3981715 species recorded in GBIF matching the query: { } The dataset's 3981715 records were derived from 62648 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0006625-230828120925497/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences